Amlapitta : A Critical Review Study - Bhati, Lokesh Singh; Sharma, Madan Mohan; Porwal, Rohit R (International Research Journal of Ayurveda & Yoga, 2020)
In Veda no indicative situations were found about Amlapitta as a illness. Charak, Sushruta and Vagabhata has not described the Amlapitta as diseases article. Firstly Aacharya Kashayap, Harita, Madhav described the Amlapitta. Amlapitta is stomach oriented, and Kapha Pitta are the dominating Dosha. Amlapitta is disease, which is characterized by the cardinal symptoms like Avipak, klam,utklesh, tikta-amla udgar, hruda kantha dah and aruchi. Dietary pattern of Indian people has been changing and upto certain extent by the influence of western culture. Irregular and untimely eating habits along with certain variations of recipes can be included under the Viruddhahar. Ashatang harudyakar quotes that the effects of Viruddhahar consumption are likely that of Garavish. Amlapitta has been included in the list of diseases of caused by Virudhaasan. Amlaguna property of the pitta is exaggerated. Amlapitta is described as a disease generally resulting after ajeerna. It is quite common disease prevailing all over the world. In this article the all information related to Amalpitta has been compiled.